2022
DOI: 10.1039/d1sc07178e
|View full text |Cite
|
Sign up to set email alerts
|

Evolution from superatomic Au24Ag20 monomers into molecular-like Au43Ag38 dimeric nanoclusters

Abstract: The work shows the evolution from monomeric Au24Au20 into dimeric Au43Ag38 nanoclusters and provides exciting opportunities for atomic manufacturing on metal nanoclusters to construct structures and functionality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 29 publications
2
35
1
Order By: Relevance
“…Moreover, the surface-atom doping has a substantial influence on the catalytic performances of the doped clusters, mainly because the chemical reactions directly occur on the surface/interface of the catalysts. Recently, it has been reported that two surface Au atoms of the Au 23 cluster were replaced by Cd atoms (i.e., Au 19 Cd 2 ), which can bring about the 2-fold increase in the CO selectivity in comparison with the parent Au 23 cluster and even gave rise to a higher activity of CO 2 RR than the currently reported clusters (Figure ). The *CO intermediate stabilization on the Au 19 Cd 2 cluster was 0.74 eV less endergonic than that on the Au 23 cluster, implying that more *CO species were yielded on the former, which was attributed to the dynamic interaction of the active S sites from Cd–S–Au staple and reaction intermediates, including the Cd–S bond cleavage upon bound with *CO and then the Cd–S–Au staple regeneration upon CO desorption.…”
Section: Electrochemical Reduction Of Co2 Over Au-based Clusterssupporting
confidence: 92%
“…Moreover, the surface-atom doping has a substantial influence on the catalytic performances of the doped clusters, mainly because the chemical reactions directly occur on the surface/interface of the catalysts. Recently, it has been reported that two surface Au atoms of the Au 23 cluster were replaced by Cd atoms (i.e., Au 19 Cd 2 ), which can bring about the 2-fold increase in the CO selectivity in comparison with the parent Au 23 cluster and even gave rise to a higher activity of CO 2 RR than the currently reported clusters (Figure ). The *CO intermediate stabilization on the Au 19 Cd 2 cluster was 0.74 eV less endergonic than that on the Au 23 cluster, implying that more *CO species were yielded on the former, which was attributed to the dynamic interaction of the active S sites from Cd–S–Au staple and reaction intermediates, including the Cd–S bond cleavage upon bound with *CO and then the Cd–S–Au staple regeneration upon CO desorption.…”
Section: Electrochemical Reduction Of Co2 Over Au-based Clusterssupporting
confidence: 92%
“…Very recently, the Zhu group reported two kinds of monomeric compounds, Au 24 Ag 20 (C 12 H 13 ) 24 Cl 2 (denoted as Au 24 Ag 20 -1; C 12 H 13 = deprotonated 4- tert -butylphenylacetylene) and Au 24 Ag 20 (C 9 H 7 ) 24 Cl 2 NCs (denoted as Au 24 Ag 20 -2; C 9 H 7 = deprotonated 2-methylphenylacetylene), as well as two kinds of dimeric compounds, Au 43 Ag 38 (C 12 H 13 ) 36 Cl 12 (denoted as Au 43 Ag 38 -1) and Au 43 Ag 38 (C 9 H 7 ) 36 Cl 9 (denoted as Au 43 Ag 38 -2) NCs . The monomeric bimetal NCs afforded similar core structures, including a hollow Au 12 icosahedron surrounded by Ag 20 .…”
Section: Metal Ncs For Co2rrmentioning
confidence: 99%
“…(e) FEs for CO 2 RR products obtained on Au 43 Ag 38 . Reprinted with permission under a Creative Comments Attribution-Noncommercial 3.0 Unported License from ref . Copyright 2022 Royal Society of Chemistry.…”
Section: Metal Ncs For Co2rrmentioning
confidence: 99%
“…2c and d, there is only one kind of surface motif in both NCs, namely AuL 2 (L = 4-tert-butyl phenylacetylene, or 3,3-dimethyl-1butyne) with a linear staple structure, in good agreement with previous findings by Zheng's group and Zhu's group. 31,37 On the basis of the coordination modes of the alkynyl ligands on the metal core surface, for NC 1, the six pairs of staple " t BuPh-CuC-Au-Ph-CuC t Bu" motifs on the cluster show four different binding motifs on Ag 5 faces (demonstrated in Fig. S5 †), whereas the " t BuCuC-Au-CuC t Bu" motifs in NC 2 display three kinds of binding motifs (Fig.…”
Section: Paper Dalton Transactionsmentioning
confidence: 99%